1989
DOI: 10.1111/j.1365-2125.1989.tb03593.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibition and cerebral circulation‐a review.

Abstract: 1. The identification of a vascular wall renin angiotensin system and of angiotensin converting enzyme on the luminal surface of the endothelium in many tissues, including the brain, has stimulated research on the influence of the renin angiotensin system on regional blood flows. 2. In experimental studies inhibition of the angiotensin converting enzyme shifts the limits of cerebral blood flow autoregulation towards lower blood pressure values. 3. In patients with chronic arterial hypertension and in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…318 Consistent with this, studies by Waldemar 20 and Waldemar and Paulson 21 showed that angiotensin-converting enzyme inhibitors increase CBF at lower blood pressure levels. Rajagopalan et al 22 have suggested that captopril may increase CBF in patients with congestive heart failure by decreasing central sympathetic tone.…”
Section: Discussionsupporting
confidence: 65%
“…318 Consistent with this, studies by Waldemar 20 and Waldemar and Paulson 21 showed that angiotensin-converting enzyme inhibitors increase CBF at lower blood pressure levels. Rajagopalan et al 22 have suggested that captopril may increase CBF in patients with congestive heart failure by decreasing central sympathetic tone.…”
Section: Discussionsupporting
confidence: 65%
“…However, dur ing a reduction in blood pressure, the greater dila tory capacity of the smaller vessels would shift the lower limit of autoregulation. The experimental re sults were supported by several clinical studies of the effect of acute or chronic ACE inhibition on CBF (reviewed by Waldemar and Paulson, 1989). In all reports, CBF remained constant, or was slightly increased, despite a significant reduction of MABP (Rajagopalan et al, 1984;Frei and Muller-Brand, 1986;Paulson et al, 1986;Minematsu et al, 1987;Waldemar et al, 1989a).…”
Section: Discussionsupporting
confidence: 55%
“…33,36,37 Experiments using captopril and other angiotensin-converting enzyme inhibitors suggest that this feature also occurs with the activation of the renin-angiotensin system. 33,38,39 Nitric oxide also plays a major role in maintaining the cerebral vasculature in a dilated state. 40 Presently, evidence indicates that the maintenance of renal perfusion in cirrhosis with ascites is critically dependent on the intrarenal synthesis of prostaglandins 41 and nitric oxide 42 and on the circulating plasma levels of natriuretic peptides, 43 which are powerful renal vasodilators.…”
Section: Discussionmentioning
confidence: 99%